Interaction of protons with nuclei in the Born approximation (I) - Yu. A. Berezhnoy; V. A. Zolotarev; V. P. Mikhailyuk (Ядерна фізика та енергетика)
Based on the Born approximation an approach that allows studying the processes of particle-nucleus interaction in the intermediate energy region has been developed. In contrast to the approach, presented in our previous papers, where analytical expressions for polarization observables for elastic proton scattering by nuclei were obtained using the expansion of the potential into the series up to the first significant terms, in this approach, the decomposition of such potential was not used. When obtaining analytical expressions for the amplitudes for elastic scattering of protons by nuclei, the second Born approximation with a potential in the Woods - Saxon form, as well as with the potential with a sharp absorption boundary, which was corrected to take into account the blurring of the nuclear surface, are used.